Uji Potensi Antibakteri Ekstrak Metanol Jeroan dan Daging Teripang Bola (Phyllophorus sp.) Terhadap Bakteri Escherichia coli dan Staphylococcus aureus - Windy Widyowati; Misbakhul Munir; Dian Sari Maisaroh (Journal of Natural Sciences, 2023)
Pathogenic bacteria can cause disease problems such as diarrhea, vomiting, typhus, gastrointestinal infections, and other diseases. Escherichia coli and Staphylococcus aureus are the smallest types of pathogenic bacteria in the world. Efforts to overcome the presence of bacteria required antibacterial. This study aims to determine the antibacterialpotential of methanol extract of giblets and meat of sea cucumber balls (Phyllophorus sp.) againstbacteria called Escherichia coli and Staphylococcus aureus through the inhibition zones formed and to determine differences in the effect of the inhibition zones between offal extracts and sea cucumber meat (Phyllophorus sp.). The results of this antibacterial potential showed a clear zone of inhibition around the disc paper. The inhibition zones of offal extract and sea cucumber meat (Phyllophorus sp.) were observed at 1x24 hours and 2x24 hours. Based on measurements using a vernier caliper on extracts of sea cucumber offal and meat (Phyllophorus sp.) obtained a value below 5 mm, it was stated that the resulting inhibition zone was classified as weak. Based on the results of the SPSS 16 one-way ANOVA test, there was no difference in the clear zone, because the test results showed P 0.05, so there was no significant difference.